2016
DOI: 10.1021/acs.est.6b02938
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Demand: The Anthropogenic and Climatic Drivers of Urban Water Consumption

Abstract: Cities in drought prone regions of the world such as South East Australia are faced with escalating water scarcity and security challenges. Here we use 72 years of urban water consumption data from Melbourne, Australia, a city that recently overcame a 12 year "Millennium Drought", to evaluate (1) the relative importance of climatic and anthropogenic drivers of urban water demand (using wavelet-based approaches) and (2) the relative contribution of various water saving strategies to demand reduction during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
1
11
0
1
Order By: Relevance
“…Given a large population, population density and economic development are the main influences on water demand, whereas reservoir storage and precipitation are the main influences on water supply. Similar to the results of Hemati, Rippy, Grant, Davis, and Feldman (), population density mainly affects water demand and thus reduces the resilience of water quantity. Because of a high population density along the coast, water resources per capita were lower in these areas than in other areas, coinciding with lower resilience of water quantity.…”
Section: Resultssupporting
confidence: 81%
“…Given a large population, population density and economic development are the main influences on water demand, whereas reservoir storage and precipitation are the main influences on water supply. Similar to the results of Hemati, Rippy, Grant, Davis, and Feldman (), population density mainly affects water demand and thus reduces the resilience of water quantity. Because of a high population density along the coast, water resources per capita were lower in these areas than in other areas, coinciding with lower resilience of water quantity.…”
Section: Resultssupporting
confidence: 81%
“…The Thomson reservoir was added in 1984 with the intention to drought-proof Melbourne, increasing storage capacity by around 250%. However, the additional storage led to more competition for water, as well as population and industrial growth, and subsequently significant increases in water demand were seen 47 . In 1984, the total water use was around three times higher than that in the 1940's (Fig.…”
Section: Supply-demand Cyclesmentioning
confidence: 99%
“…In Melbourne, for example, the addition of reservoirs prevented water shortages only during minor drought conditions 47 In Athens, the Mornos reservoir overflowed in 1985. This event created pride and political enthusiasm among the population, as Athens had -for the first time since becoming capital of the Greek state-more water available than needed 40 .…”
Section: Reservoir Effectsmentioning
confidence: 99%
“…In Melbourne (Australia), Hemati et al (2016) evaluate the relative importance of the climatic and anthropogenic drivers of urban water demand (using wavelet-based approaches) and the relative contribution of various water saving strategies to demand a reduction in water use during the millennium drought. They concluded that the main dominant driver was urban water savings (69%), followed by a 'non-revenue' water reduction (29%) and potable substitution with alternative sources such as rain or recycled water (3%).…”
Section: Water Consumption and Climatic Factorsmentioning
confidence: 99%